MENGKOMUNIKASIKAN PERCERAIAN KEPADAANAK - Siti Hikmah Anas (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2011)
Divorce of parents brings much negative impad on children. However, it can be minimized by creating an optimal environment. Although it is notalways easily achieved by the parents, an optimal environment is very importantforfuture development of their children. Communicating the divorce to the children is not an easy thing for parents. It takes courage to hold back anger, the courage to say what adually happens, the choice of the language appropriate to the psychology of children, and the ability to find the right time. Communicating it properly will reduce the psychological impad on children afterthe divorce of their parents.